2016
DOI: 10.21134/haaj.v16i2.268
|View full text |Cite
|
Sign up to set email alerts
|

Factores de riesgo para ludopatia en un grupo de jugadores de casinos de la ciudad de Medellín, Colombia

Abstract: ResumenRecently, the diagnostic manual of mental disorders, American Psychiatric Association -DSM-V has included pathological gambling as an entity with nosology, not only by the high prevalence rates that begin to occur in the general population, but also by the impact it has on the mental health of sufferers. This qualitative research, I seek to identify through a semistructured interview, the risk factors that led to a group of 50 players casino, to end this dependence is not chemistry, prominent among them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
4
0
3
Order By: Relevance
“…As for psychological factors, a study conducted on participants with problems with gambling behavior found that these people have difficulties initiating affective relationships and that they present affective instability, introversion, insecurity about expressing feelings, and emotional dependence (Castaño, Calderón, & Restrepo, 2016). It has also been found that gambling disorder is associated with the presence of obsessive-compulsive disorder, anxiety, and depression (Hodgins et al, 2012).…”
Section: Factors and Consequences Related To Gambling Disordermentioning
confidence: 99%
See 3 more Smart Citations
“…As for psychological factors, a study conducted on participants with problems with gambling behavior found that these people have difficulties initiating affective relationships and that they present affective instability, introversion, insecurity about expressing feelings, and emotional dependence (Castaño, Calderón, & Restrepo, 2016). It has also been found that gambling disorder is associated with the presence of obsessive-compulsive disorder, anxiety, and depression (Hodgins et al, 2012).…”
Section: Factors and Consequences Related To Gambling Disordermentioning
confidence: 99%
“…As for the socio-environmental factors related to the availability of gambling and places for gambling, it has been found that the increase in gambling disorder is related to the availability of casinos, slot machines, and gambling halls (Castaño et al, 2016). In the particular case of Mexico, as of May 2018, the Secretaría de Gobernación (2018) had registered in the General Directorate of Games and Draws only 33 permit holders of number draws and betting centers (casinos), representing a total of 326 establishments in operation nationwide.…”
Section: Factors and Consequences Related To Gambling Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…La adicción sin drogas es una conducta repetitiva que produce placer y alivio de tensión, la cual lleva a una pérdida de control de la conducta (Cía, 2014). (Castaño, Calderón & Restrepo, 2016;Morales et al, 2015;Oropeza et al, 2016).…”
unclassified